Impact of a standardized protocol for the Management of Prolonged Neonatal Jaundice in a regional setting: an interventional quasi-experimental study - Hui-Siu Tan; Inthira-Sankari Balasubramaniam; Amar-Singh HSS; May-Luu Yeong; Chii-Chii Chew; Ranjit-Kaur Praim Singh; Ai-Yuin Leow; Fatimahtuz-Zahrah Muhamad Damanhuri; Santhi Verasingam (BMC, 2019)
Abstract Background Prolonged neonatal jaundice (PNNJ) is often caused by breast milk jaundice, but it could also point to other serious conditions (biliary atresia, congenital hypothyroidism). When babies with PNNJ receive a routine set of laboratory investigations to detect serious but uncommon conditions, there is always a tendency to over-investigate a large number of well, breastfed babies. A local unpublished survey in Perak state of Malaysia revealed that the diagnostic criteria and initial management of PNNJ were not standardized. This study aims to evaluate and improve the current management of PNNJ in the administrative region of Perak. Methods A 3-phase quasi-experimental community study was conducted from April 2012 to June 2013. Phase l was a cross-sectional study to review the current practice of PNNJ management. Phase ll was an interventional phase involving the implementation of a new protocol. Phase lll was a 6 months post-interventional audit. A registry of PNNJ was implemented to record the incidence rate. A self-reporting surveillance system was put in place to receive any reports of biliary atresia, urinary tract infection, or congenital hypothyroidism cases. Results In Phase I, 12 hospitals responded, and 199 case notes were reviewed. In Phase II, a new protocol was developed and implemented in all government health facilities in Perak. In Phase III, the 6-month post-intervention audit showed that there were significant improvements when comparing mean scores of pre- and post-intervention: history taking scores (p < 0.001), family history details (p < 0.05), physical examination documentation (p < 0.001), and total investigations done per patient (from 9.01 to 5.81, p < 0.001). The total number of patient visits reduced from 2.46 to 2.2 per patient. The incidence of PNNJ was found to be high (incidence rate of 158 per 1000 live births). Conclusions The new protocol standardized and improved the quality of care with better clinical assessment and a reduction in unnecessary laboratory investigations. Trial registration Research registration number: NMRR-12-105-11288.